Efektivitas Kelas Parenting di Pusat Pembelajaran Keluarga - Amanda, Lucy Cita Widya; Priambodo, Bayu (SOCIETAS, 2024)
The rise in cases of violence against children in the city of Surabaya can be caused by a lack of parental care for children. For this reason, the Surabaya Government formed the Family Learning Center (PUSPAGA) with a parenting class program. The aim of this research is to find out whether parenting classes are effective in improving parents' abilities and understanding regarding better parenting that is appropriate to current developments and children's needs. The research method used is descriptive qualitative. This research uses primary data obtained through interviews and observations and secondary data originating from books, articles and journals. The data analysis technique uses analysis according to the views of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results of the research show that the effectiveness of parenting classes in improving child rearing patterns in Peneleh Subdistrict, Surabaya City has been running effectively, which can be seen from the effectiveness indicators according to Campbell, including the success of programs/activities, success of targets/aims, satisfaction with programs/activities, overall achievement of goals. comprehensive. Apart from that, there are inhibiting and supporting factors in implementing parenting classes. Supporting factors include community participation in taking parenting classes, professional natural resources in line with family learning experts, and ease of finding information. Then the inhibiting factors for parenting classes are the time and implementation of parenting classes.